2010
DOI: 10.1007/s00128-010-0027-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Pesticide Use in Agriculture and Adverse Birth Outcomes in Brazil: An Ecological Study

Abstract: This ecological study analyzed the association between pesticide use and prematurity, low weight and congenital abnormality at birth, infant death by congenital abnormality, and fetal death in Brazil in 2001. Simple linear regression analysis has determined a positive association between pesticide use and prematurity, low birth weight, and congenital abnormality. The association between pesticide use and low birth weight (p = 0.045) and, congenital abnormality (p = 0.004) and infant death rate by congenital ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
22

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 10 publications
0
10
0
22
Order By: Relevance
“…Por outro lado, não foi observado um padrão similar em relação ao baixo peso ao nascer, o qual tem sido associado com a exposição a agrotóxicos, tanto no Brasil 23 , como em outros países 15,29,30,31 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Por outro lado, não foi observado um padrão similar em relação ao baixo peso ao nascer, o qual tem sido associado com a exposição a agrotóxicos, tanto no Brasil 23 , como em outros países 15,29,30,31 .…”
Section: Resultsunclassified
“…A literatura científica revela a escassez de estudos ecológicos apontando para uma associação positiva entre exposição a agrotóxicos e prematuridade 9 . De Siqueira et al 23 recém-nascido. Assim, um aspecto importante do possível efeito dos agrotóxicos consiste no fato de que um aumento dos nascimentos precoces acarrete um incremento na mortalidade infantil 35 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Nevertheless, exposure assessment relied on self-report as well and results should therefore be interpreted with caution. Many studies have reported no increased risk of CAs in offspring residing in areas with pesticide use (de Siqueira et al, 2010; Marshall et al, 1997). Potential association between permethrin/benzyl benzoate lotion during pregnancy for therapeutic reasons (headlice and/or scabies treatment) and CAs was investigated in one study (Kennedy et al, 2005) concluding that no association exists and thus these pesticides are safe.…”
Section: Pesticides and Development Of Congenital Abnormalitiesmentioning
confidence: 99%
“…103 Adverse birth outcomes; ecological study: 26 Brazilian states; data from SINASC and SIM; period: 12 mo, 2009.…”
mentioning
confidence: 99%